Highly transparent and impact-resistant PMMA nanocomposites reinforced by cellulose nanofibers of pineapple leaves modified by eco-friendly methods - Y. F. Shih; M. Y. Chou; H. Y. Lian; L. R. Hsu; S. M. Chen-Wei (eXPRESS Polymer Letters)
In this study, cellulose nanofibers (CNFs) were derived from waste pineapple leaves with the aim of developing a nanocomposite with high impact strength and transparency. First, CNFs were prepared using an acid-base treatment and 2,2,6,6-tetramethylpiperidin-1-oxyl radical (TEMPO)-mediated oxidation, and then, the surface was modified with polymerized methyl methacrylate (MMA) using an eco-friendly method in an aqueous system. The MMA-modified CNF had an increased contact angle from 12.02 to 57.45°, and the surface hydrophobicity improved the interfacial compatibility between the CNF and polymethyl methacrylate (PMMA) matrix. At 1–3 wt% of the modified CNF, the impact strength of the nanocomposites was significantly improved by 2.7–22.9%. Moreover, this eco-friendly modification allowed CNFs to disperse homogeneously in the nanocomposite for excellent light transmittance. In conclusion, this eco-friendly modification can replace conventional solvent-based modification, allowing modified CNF to effectively reinforce the PMMA nanocomposite.